TRPA1 is functionally co-expressed with TRPV1 in cardiac muscle: Co-localization at z-discs, costameres and intercalated discs. Issue 5 (2nd September 2016) - Andrei, Spencer R.; Sinharoy, Pritam; Bratz, Ian N.; Damron, Derek S.
ABSTRACT: Transient receptor potential channels of the ankyrin subtype-1 (TRPA1) and vanilloid subtype-1 (TRPV1) are structurally related, non-selective cation channels that show a high permeability to calcium. Previous studies indicate that TRP channels play a prominent role in the regulation of cardiovascular dynamics and homeostasis, but also contribute to the pathophysiology of many diseases and disorders within the cardiovascular system. However, no studies to date have identified the functional expression and/or intracellular localization of TRPA1 in primary adult mouse ventricular cardiomyocytes (CMs). Although TRPV1 has been implicated in the regulation of cardiac function, there is a paucity of information regarding functional expression and localization of TRPV1 in adult CMs. Our current studies demonstrate that TRPA1 and TRPV1 ion channels are co-expressed at the protein level in CMs and both channels are expressed throughout the endocardium, myocardium and epicardium. Moreover, immunocytochemical localization demonstrates that both channels predominantly colocalize at the Z-discs, costameres and intercalated discs. Furthermore, specific TRPA1 and TRPV1 agonists elicit dose-dependent, transient rises in intracellular free calcium concentration ([Ca 2+ ]i ) that are abolished in CMs obtained from TRPA1 −/− and TRPV1 −/− mice. Similarly, we observed a dose-dependent attenuation of the TRPA1 and TRPV1 agonist-induced increase in [Ca 2+ ]i when WT CMs were pretreated with increasing concentrations of selective TRPA1 or TRPV1 channel antagonists. In summary, these findings demonstrate functional expression and the precise ultrastructural localization of TRPA1 and TRPV1 ion channels in freshly isolated mouse CMs. Crosstalk between TRPA1 and TRPV1 may be important in mediating cellular signaling events in cardiac muscle.